2016
DOI: 10.3389/fmicb.2016.01801
|View full text |Cite
|
Sign up to set email alerts
|

Biocombinatorial Synthesis of Novel Lipopeptides by COM Domain-Mediated Reprogramming of the Plipastatin NRPS Complex

Abstract: Both donors and acceptors of communication-mediating (COM) domains are essential for coordinating intermolecular communication within nonribosomal peptides synthetases (NRPSs) complexes. Different sets of COM domains provide selectivity, allowing NRPSs to utilize different natural biosynthetic templates. In this study, novel lipopeptides were synthesized by reprogramming the plipastatin biosynthetic machinery. A Thr-to-Asp point mutation was sufficient to shift the selectivity of the donor COM domain of ppsB t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…It was difficult to acquire sufficient quantities of purified lipopeptides derivatives from the engineering mutant for biological testing by isolation and separation. In previous study [ 18 ], we chemically synthesized the linear plipastatin derivative (hexapeptide: C 16 β-OHFA-Glu-Orn-Tyr-Thr-Glu-Ala/Val) from company of KareBay (Ningbo, China), and tested its antimicrobial activity. The results showed that this linear hexapeptide was inactive against bacteria, but exhibited a MIC of 62.5 μg mL −1 against Fusarium oxysporum , Rhizopus stolonifer, and Aspergillus ochraceus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was difficult to acquire sufficient quantities of purified lipopeptides derivatives from the engineering mutant for biological testing by isolation and separation. In previous study [ 18 ], we chemically synthesized the linear plipastatin derivative (hexapeptide: C 16 β-OHFA-Glu-Orn-Tyr-Thr-Glu-Ala/Val) from company of KareBay (Ningbo, China), and tested its antimicrobial activity. The results showed that this linear hexapeptide was inactive against bacteria, but exhibited a MIC of 62.5 μg mL −1 against Fusarium oxysporum , Rhizopus stolonifer, and Aspergillus ochraceus .…”
Section: Discussionmentioning
confidence: 99%
“…We recently investigated the production of bioengineered plipastatin analogs by thioesterase domain- and inter-module communication domain-mediated reprogramming of the plipastatin NRPS complex [ 18 , 19 ]. In the present study, we attempted to further modify the plipastatin amino acid core by deleting complete modules or individual domains, and subsequently evaluated the effect of these changes on the plipastatin assembly line.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutagenesis of the COM domains of rhabdopeptide/xenortide NRPS modules resulted in the change of protein affinity and the production of different peptide analogues ( Hacker et al., 2018 ). Furthermore, five novel lipopeptides (cyclic pentapeptide, linear hexapeptide, nonapeptide, heptapeptide, and cyclic octapeptide) were produced through the engineering of the COM domains of plipastatin NRPSs ( Liu et al., 2016 ), further demonstrating the importance of COM domains for the proper interactions of adjacent NRPS modules. On the other hand, the COM domains are not the only factor that influences the biosynthetic process of NRPs ( Bloudoff and Schmeing, 2017 ; Miller et al., 2016 ).…”
Section: Biocatalytic Approaches For the Synthesis Of Nrpsmentioning
confidence: 99%
“…Also, [∆Leu 6 ] surfactin showed a significant antifungal activity against Fusarium moniliforme. Liu et al (2016) were able to create novel LPs by shifting the selectivity of the donor COM domain (communication-mediating domain, essential for coordinating intermolecular communication within NRPSs complexes). Using this technique, and reprogramming the plipastatin biosynthetic machinery, five new LPs were identified.…”
Section: Nrps Engineeringmentioning
confidence: 99%